USING MUSIC AND STORYTELLING IN TEACHING ENGLISH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with the teaching process and studies using music and storytelling to young learners in teaching English to young learners. Stories and music are very important for our psychical health. We learn our mother tongue through stories. So, it is natural to learn foreign language through them as well. Teachers should try to teach their students about language, life and culture through stories.